Concentration of PM2,5 and Characteristic Analysis of Workers with Health Complaints Smoked Fish Workers in Tambak Wedi Village Surabaya - Dwi Sinta Nirmala; Corie Indria Prasasti (Universitas Airlangga, 2015)
Abstract: Smoked fish in Tambak Wedi village Surabaya using coconut shell as the main fuel. Combustion of coconut shell in the process of smoked fish produced pollutants PM2,5 that can cause health problems for workers. The purpose of this study was to measure the consentration of PM2,5 and identify worker characteristics that affect worker health complaints in the smoked fish Tambak Wedi Village Surabaya.This study was observational descriptive study used cross sectional design. This study was conducted on June, 2014 by using questionnaire, interview, and observation with the sample was 26 respondents. The independent variables were PM2,5, age, year of works, lenght of employment, medical history, use of PPE and work position. PM2,5 measurement using a Haz-Dust EPAM 5000 for an hour and data collection characteristics of workers using a questionnaire and interview method. The results of the study, it found that concentration of PM2,5 at 8 location of Tambak Wedi village smoked fish exceed environmental requirements. Health complaints experienced by workers in the form of eye complaints, highest perceived by workers were an eye sore (100%), while the highest respiratory complaints perceived by workers were shortness of breath (80.8%). Worker at smoked fish have chance to get respiratory problems and eye irritation. The suggestion for workers must use PPE, use chimney and check their health periodically to health clinics in Tambak Wedi Surabaya.Keywords: Smoked fish, PM2,5, health complaints